Development of an E-Thesis Application Using Agile Method and Azure Devops at XYZ University - Kanyadian Idananta; Mayliana Mayliana; Livia Ashianti (Syntax Corporation, 2026)
To adapt to rapid change in the software development landscape, organizations require a more adaptive approach than the traditional Waterfall method to better accommodate evolving user needs. The Agile methodology, characterized by its adaptive, iterative, and responsive nature, is well-suited for modern application development environments. However, Agile has notable weaknesses in operational aspects such as deployment, monitoring, and the lack of continuous testing and integration. To overcome these limitations, the implementation of Agile methods is increasingly complemented by DevOps practices. Integrating Agile and DevOps methodologies accelerates product delivery, improves communication and team collaboration, and automates development processes. Universitas XYZ developed a web-based e-Thesis application to integrate and monitor all stages of thesis supervision using the Agile methodology, specifically the Scrum framework, supported by DevOps practices implemented through the Azure DevOps platform. Azure DevOps supports a collaborative culture and provides a set of integrated processes that bring together developers, project managers, and contributors. This study demonstrates that the integration of the Agile methodology with the Azure DevOps platform in the development of the e-Thesis system has proven effective in enabling faster, more reliable, and responsive system development aligned with user requirements.